Serum Metabonomics Reveals Risk Factors in Different Periods of Cerebral Infarction in Humans - Chen, Guoyou; Guo, Li; Zhao, Xinjie; Ren, Yachao; Chen, Hongyang; Liu, Jincheng; Jiang, Jiaqi; Liu, Peijia; Liu, Xiaoying; Hu, Bo; Wang, Na; Peng, Haisheng; et al. (Frontiers in Molecular Biosciences, 2022)
Studies of key metabolite variations and their biological mechanisms in cerebral infarction (CI) have increased our understanding of the pathophysiology of the disease. However, how metabolite variations in different periods of CI influence these biological processes, and whether key metabolites from different periods may better predict disease progression is still unknown. We performed a systematic investigation using the metabonomics method. Various metabolites in different pathways were investigated in serum from 143 patients diagnosed with CI and 59 healthy controls. Phe-Phe, Carnitine C18:1, palmitic acid, cis-8,11,14-Eicosatrienoic acid, palmitoleic acid, 1-Linoleoyl-rac-glycerol, MAG 18:1, MAG 20:3, phosphoric acid, 5a-dihydrotestosterone, Ca, K and GGT were the major components in the early period of CI. GCDCA, glycocholate, PC 36:5, LPC 18:2 and PA showed obviously changes in intermediate time. In contrast, trans-vaccenic acid, linolenic acid, linoleic acid, all-cis-4,7,10,13,16-docosapentaenoic acid, arachidonic acid, DHA, FFA 18:1, FFA 18:2, FFA 18:3, FFA 20:4, FFA 22:6, PC 34:1, PC 36:3, PC 38:4, ALP and Crea displayed changes in the later time. More importantly, we found that phenylalanine metabolism, medium-chain acylcarnitines, long-chain acylcarnitines, choline, DHEA, LPC 18:0, LPC 18:1, FFA 18:0, FFA 22:4, TG, ALB, IDBIL and DBIL played vital roles in the development of different periods of CI. Increased phenylacetyl-L-glutamine was detected and may be a biomarker for CI. It was of great significance that we discovered key metabolic pathways and risk metabolites in different periods of CI different from those previously reported. The specific data are detailed in the section of conclusion. Just as important, we also explored metabolites difference of CI patients complicated with high blood glucose compared with healthy controls. Further work in this area may inform personalized treatment approaches in clinical practice for CI by elucidating the pathophysiological mechanisms experimentally.